STUDY CHEMICAL ADDITIVES POLYPLAST C-3 ON THE PROPERTIES OF PORTLAND CEMENT (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article presents the results of research work on the development of the properties of binders with chemical additives and determines the optimal compositions.Today, along with water, filler and binder, additives have become an indispensable component of the concrete mix. Among the many types of chemical additives, plasticizers occupy a separate place, especially the most effective of them are superplasticizers. Below are considered the most important physical and mechanical characteristics of cement kiln, which can be influenced by the introduction of additives. This will serve as a basis for understanding the behavior of cement, concrete mix and concrete obtained with the use of different types of additives, which will be devoted to the following chapters.